Research Trends in Teacher Agency: A Bibliometric Analysis From 1995 to 2023 - Yumei Fan; Jiayou Zhu (SAGE Open)
This study adopts bibliometric analysis to examine the development of teacher agency studies from 1995 to 2023. A total of 346 publications were retrieved from the Social Science Citation Index and Arts & Humanities Citation Index and analyzed using VOSviewer software. The results indicate that research on teacher agency has undergone three distinct periods and continues to show an upward trend. Key scholars and highly cited publications are identified, along with the most prolific areas of research. The analysis categorizes the topics on teacher agency research into an emergent framework consisting of individual, micro-, meso-, exo-, and macro-level dimensions. Additionally, the temporal analysis reveals that increasingly varied contexts have enriched the discourse on teacher agency, with topics being influenced by broader social contexts.